(untitled) (Ukrainian Journal of Ophthalmology, 2025)
Introduction. Accommodative insufficiency (AI) is a non-strabismic binocular vision anomaly characterized by an inability to focus for near vision, with symptoms of blurred near vision, headache, visual fatigue, and asthenopic symptoms. Purpose. To evaluate the efficacy of Plus Lens treatment, and Flipper glasses in the improvement of Accommodative Amplitude (AA) and Near Point of Accommodation (NPA) in Accommodative insufficiency (AI). Methods. A prospective study of 50 children aged 8-15years with distance heterophoria (< 2 pd), near heterophoria(< 6 pd), Near Point of Convergence (NPC) (10 cm/better on Royal Air Force (RAF) rule), and NPA (worse than 10 cm, 15d – 2.5* age) were recruited during July 2018 to June 2019 and followed up for 3months. Measurements including NPC, NPA, and AA were measured in each eye of the Plus Lens Reading Addition(PLRA) and Flipper group. Results. Accommodative Insufficiency is higher in female children 67% in PLRA and 60% in the Flipper group with a mean age of 12.73 years in the PLRA group and 12.93 years in the Flipper group. NPA improved from 15.07 cm to 14.4 cm at 4 weeks, 11.87 cm at 8 weeks, and 9.33 cm at 12 weeks of treatment with PLRA. The NPA improved from 15.73 cm to 12.4 cm at 4 weeks, 10.93 cm at 8 weeks, and 8.27 cm at 12 weeks of treatment with Flipper glasses. AA improved from 6.73 D to 7.03 D at 4 weeks, 8.5 D at 8 weeks, and 10.73 D at 12 weeks of treatment with PLRA. The AA improved from 6.33 D to 8.03 D at 4 weeks, 9.13 D at 8 weeks, and 11.73 D at 12 weeks of treatment with Flipper glasses. Children reported good compliance and no longer experienced blur or headache. Conclusion. A higher level of improvement in NPA and AA is observed in the Flipper group. Faster improvement is seen in the Flipper group, and treatment time needed will be shorter in the Flipper group, but it is more difficult to motivate subjects to do orthoptic exercises as compared to wearing reading glasses.